2013
DOI: 10.2308/acch-50486
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Diverse Boards and Properties of Analyst Earnings Forecasts

Abstract: SYNOPSIS Using a sample of 2,200 U.S. listed firm-year observations (2001–2007), this study shows a positive (negative) relation between gender diversity on corporate boards and analysts' earnings forecast accuracy (dispersion), after controlling for earnings quality, corporate governance, audit quality, stock price informativeness, and potential endogeneity. Our findings are important as they suggest that board diversity adds to the transparency and accuracy of financial reports such that earni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
167
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(190 citation statements)
references
References 65 publications
18
167
2
3
Order By: Relevance
“…Yet empirical studies also suggest the importance of gender diversity in producing a better perspective, and hence contributing to better financial performance (Dobbin & Jung, 2011;Gul, Hutchinson & Lai, 2013;Marinova, Plantenga & Remery, 2010;Rose, 2007). In a similar vein, Dezsö and Ross (2012), Rose (2007) and Smith et al (2006) also found that gender diversity was positively related to the firm's performance in emerging economies.…”
Section: Introductionmentioning
confidence: 95%
“…Yet empirical studies also suggest the importance of gender diversity in producing a better perspective, and hence contributing to better financial performance (Dobbin & Jung, 2011;Gul, Hutchinson & Lai, 2013;Marinova, Plantenga & Remery, 2010;Rose, 2007). In a similar vein, Dezsö and Ross (2012), Rose (2007) and Smith et al (2006) also found that gender diversity was positively related to the firm's performance in emerging economies.…”
Section: Introductionmentioning
confidence: 95%
“…A considerable body of work has suggested that board gender diversity affects board dynamics, decision making, monitoring, and in turn, affects firm outcomes. Specifically, Gul, Hutchinson and Lai (2013) documented that the gender diversity of boards may lead to more board discussion and monitoring of company issues, inducing managers to disclose more information on the operations, transactions, and strategy. Higgs (2003) and Tyson (2003) argued that gender diversity may improve board effectiveness, organisational value, and performance by offering new insights and perspectives.…”
Section: Other Rmc Human Capital Characteristics -Gender Diversitymentioning
confidence: 99%
“…Yöneticilerdeki farklılıklar, özellikle de muhafazakarlık, riskten kaçınma ve etik davranış gibi özellikler finansal raporlamanın kalitesini etkileyebilir (Gul, Hutchinson, & Lai, 2013 Beasley (1996) yönetim kurulu yapısı ve muhasebe hileleri konusunu incelemiştir.…”
Section: Yönetim Kurulu Büyüklüğüunclassified